Unsung interpreters: the jumbled practice of language translation in contemporary field research – a study of anthropological field sites in the Arab League countries. (3rd September 2019) - Sepielak, Katarzyna; Wladyka, Dawid; Yaworsky, William
ABSTRACT: Despite some recent criticism, the idea of language interpreting in anthropological (among others) field research seems still firmly rooted in classical anthropology where the interpreter was an obstacle and necessary evil rather than aid. We surveyed anthropologists conducting field research in Arab League countries to describe their practices and give them voice in the matter. We found that while a share of anthropologists appreciates interpreters' input, an equally striking number does not even recognize they used one. We discuss practices of having team members and local officials working as courtesy interpreters and its effect on ethics, safety and validity of data collection.